السّخرية باعتبارها موجّها للحكي في "المنام الكبير" لركن الدين الوهراني (مجلة الواحات للبحوث والدراسات, 2021)
Irony Is The Most Effective Face Criticism Of Injustice And Oppression And Repression In Various Image And Highlight Paradoxically And Contradiction In What Must Be, And What Is Actually On The Level Of Reality, The Texts Have Been "The Wahrani" This Human Dimension And Spiritual Humor In Many Works Inspired By Levantine Spirit ( Arabic) In Expressing Tasmat Reality And Contradictions And Paradoxes Of Life In Various Forms.And Either The Wahrani, Affecting All His Satirical Narrative Irony Tendency, And Embody The Spirit Of The Joust In The Then Embattled Reality Critique Tendency Detector, For Example, In Trying To "Pajamas" To Express The Concepts Of The Human Condition And Nature And Life, In Every Sense Of Irony Weghraaebih, Comic Interventions, The Nature Of Meditation And Philosophical Visions Floodlights And Is Often Used In Most Of His Creations To Actually Owed, Stereotyped Characters And Through Atypical, Using It To Reflect That Reality And Express, Through Which Private Area Divests Then Scurrying In Sarcasm And Biting Transmitting Position To A High Degree Of Humour Ironic Situation, Time And Logic. He Sometimes Resorts To Sarcasm Black That Makes Us Laugh, And At The Same Time "It Tears From Us, Or From Inside The Heads Heavy Dramatic, Like A Seething Caldron, And Soon Come Out Of It Strong Time Ridiculous Steam Before It Explodes Into The Faces Of Boiler Caused This Boiling.The Article Speaks Of Irony As Directed Llhaki, Try Exploring The Narrative Theme Components Like Inception And Its Relationship To The Body, To Indicate Initialization And Privacy With Reference To The Relationship Between The Light And The Matn And Conclusion, Focusing On Mechanisms Involving Text, As A Text Has Privacy In The Narrative.Keys-Ridiculous Do Direct Storytelling- The Narrative Pattern Components- Commence Relationship Board- Privacy Of The Signal Between The Light And The Finale.